The territorial structure and the territorial policy in Vietnam in the 21st century - Duy, Pham (Studia Mundi – Economica, 2018)
The paper aims to identify the characteristics of Vietnam's territorial structure including regional development trends, national development progress, and local development challenges. Then, it will exploit the territorial policy of the nation including the trajectory of territorial policy since the 1980s and the enforcement of these policies under local governments. It not only contributes a holistic perception on territorial structure but also supplies a historical review on regional development policy since Doimoi1 in Vietnam.
Keywords: territorial structure; regional policy; Vietnam